Pepsin Aided Extraction of Gelatin From Goat Skin - C.M. Nishanthika Jesslyn; V. Leela; G. Suganya; K.G. Tirumurugaan; H. Pushkin Raj (The Indian Veterinary Journal, 2024)
The study was designed to evaluate the effect of pepsin on the extraction of gelatin from goat skin. The goat skin was treated with pepsin at levels of 5 and 10 U/g of tissue and its effect on gelatin yield, pH and bloom strength were studied. The yield of gelatin was 10.12 % for the control group and 12.6 % and 16.5 % for the pepsin pretreated groups at 5 and 10 U respectively. There was no significant difference in the pH of gelatin among the control and pepsin treated groups. However, there was a significant decrease (P